Dropping in on the lipid droplet- tumor protein D52 (TPD52) as a new regulator and resident protein. (2nd July 2016) - Chen, Yuyan; Frost, Sarah; Byrne, Jennifer A.
ABSTRACT: Lipid droplets are essential for both the storage and retrieval of excess cellular nutrients, and their biology is regulated by a diverse range of cellular proteins, some of which function at the lipid droplet. Numerous studies have characterized lipid droplet proteomes in different organisms and cell types, and RNAi whole genome screening studies have examined the genetic regulation of lipid storage in C. elegans and D. melanogaster . While tumor protein D52 (TPD52) did not emerge from earlier studies as a strong candidate, exogenous expression of human TPD52 in cultured cells resulted in significantly increased numbers of lipid droplets, and oleic acid supplementation increased TPD52 detection at both lipid droplets and the Golgi apparatus. These results suggest that direct testing of proteins that are infrequently but recurrently identified in proteomic and RNAi screening studies may identify novel lipid droplet regulators. While the analysis of these possibly lower-abundance or itinerant lipid droplet proteins may be more technically challenging, such proteins could facilitate a more detailed interrogation of emerging aspects of lipid droplet biology.